The combination of coffee compounds attenuates early fibrosis-associated hepatocarcinogenesis in mice: involvement of miRNA profile modulation - Romualdo, Guilherme Ribeiro [UNESP]; Prata, Gabriel Bacil [UNESP]; da Silva, Tereza Cristina; Evangelista, Adriane Feijó; Reis, Rui Manuel; Vinken, Mathieu; Moreno, Fernando Salvador; Cogliati, Bruno; Barbisan, Luís Fernando [UNESP] (Elsevier, 2020)
Aberrant microRNA expression implicates on hepatocellular carcinoma (HCC) development. Conversely, coffee consumption reduces by ~40% the risk for fibrosis/cirrhosis and HCC, while decaffeinated coffee does not. It is currently unknown whether these protective effects are related to caffeine (CAF), or to its combination with other common and/or highly bioavailable coffee compounds, such as trigonelline (TRI) and chlorogenic acid (CGA). We evaluated whether CAF individually or combined with TRI and/or CGA alleviates fibrosis-associated hepatocarcinogenesis, examining the involvement of miRNA profile modulation. Then, male C3H/HeJ mice were submitted to a diethylnitrosamine/carbon tetrachloride-induced model. Animals received CAF (50 mg/kg), CAF+TRI (50 and 25 mg/kg), CAF+CGA (50 and 25 mg/kg) or CAF+TRI+CGA (50, 25 and 25 mg/kg), intragastrically, 5×/week, for 10 weeks. Only CAF+TRI+CGA combination reduced the incidence, number and proliferation (Ki-67) of hepatocellular preneoplastic foci while enhanced apoptosis (cleaved caspase-3) in adjacent parenchyma. CAF+TRI+CGA treatment also decreased hepatic oxidative stress and enhanced the antioxidant Nrf2 axis. CAF+TRI+CGA had the most pronounced effects on decreasing hepatic pro-inflammatory IL-17 and NFκB, contributing to reduce CD68-positive macrophage number, stellate cell activation, and collagen deposition. In agreement, CAF+TRI+CGA upregulated tumor suppressors miR-144-3p, miR-376a-3p and antifibrotic miR-15b-5p, frequently deregulated in human HCC. CAF+TRI+CGA reduced the hepatic protein levels of pro-proliferative EGFR (miR-144-3p target), antiapoptotic Bcl-2 family members (miR-15b-5p targets), and the number of PCNA (miR-376a-3p target) positive hepatocytes in preneoplastic foci. Our results suggest that the combination of most common and highly bioavailable coffee compounds, rather than CAF individually, attenuates fibrosis-associated hepatocarcinogenesis by modulating miRNA expression profile.
Keywords: Caffeine; Chlorogenic acid; Hepatocarcinogenesis; Liver fibrosis; miRNA; Trigonelline